Exploring the use of speculative design as a participatory approach to more inclusive policy-identification and development in Malaysia. (July 2022) - Tsekleves, Emmanuel; Ling Lee, Clarissa Ai; Yong, Min Hooi; Lau, Sian Lun
Abstract : This Case Study paper presents the first exploration of Speculative Design as a participatory democracy method for navigating the future of ageing in Malaysia. Speculative Design in the context of Global South is emerging, but without much data on how it is applied within different socio-economic conditions from the Global North countries. This Case Study considers the challenges and opportunities of employing Speculative Design as policy identification and development method from the context of Malaysia, a Global South country with its own unique characteristics. The paper concludes by suggesting that the novelty of Speculative Design as a policy-design approach in Global South countries, such as in Malaysia, requires the right selection of provocations and culturally familiar content to ease introduction of the methodology. Also, the efficacy of this approach as a participatory design application would require further enculturation within targeted communities, as well as sustained engagement through Champions. Highlights: Employing Speculative Design in a Global South context requires adaptation to local contexts. Future thinking is unfamiliar to many societies still facing non-equitable development. Participatory Speculative Design can disrupt the top-down policy-making in Malaysia. More research is required to better localize and measure the proposed method impact.